Scribal memory and word selection: text criticism of the Hebrew Bible - Person, Raymond F. (Text-Critical Studies, 2023)
Cover -- Contents -- Preface and Acknowledgments -- Note on Transcription Conventions -- Abbreviations -- Introduction -- 1. Word Selection in Conversation and Oral Traditions As A Lens to Understanding Text-Critical Variants -- 2. Category-Triggering and Text-Critical Variants -- 3. Sound-Triggering and Text-Critical Variants -- 4. Visual-Triggering and Text-Critical Variants -- 5. Text-Critical Variants and Category-Triggering, Sound-Triggering,and Visual-Triggering: Conclusions and Implications -- Bibliography -- Ancient Sources Index -- Modern Authors Index.